A molecular approach to arthrotardigrade phylogeny (Heterotardigrada, Tardigrada). (8th December 2016) - Fujimoto, Shinta; Jørgensen, Aslak; Hansen, Jesper G.
Abstract : The marine order Arthrotardigrada (class Heterotardigrada, phylum Tardigrada) is known for its conspicuously high morphological diversity and has been traditionally recognized as the most ancestral group within the phylum. Despite its potential importance in understanding the evolution of the phylum, the phylogenetic relationships of Arthrotardigrada have not been clarified. This study conducted molecular phylogenetic analyses of the order encompassing all families except Neoarctidae using nuclear 18S and 28S rRNA fragments. Data from two rare families, Coronarctidae and Renaudarctidae, were included for the first time. The analyses confirmed the monophyly of Heterotardigrada and inferred Coronarctidae as the sister group to all other heterotardigrade taxa. Furthermore, the results support a monophyletic Renaudarctidae + Stygarctidae clade, which has been previously suggested on morphology. Our data indicated that two subfamilies currently placed in Halechiniscidae are only distantly related to this family. We propose that these taxa are each elevated to family level (Styraconyxidae (new rank) and Tanarctidae (new rank)). The morphology of tardigrades is discussed in the context of the inferred phylogeny.